2022
DOI: 10.7150/ijbs.68992
|View full text |Cite
|
Sign up to set email alerts
|

TBC1D14 inhibits autophagy to suppress lymph node metastasis in head and neck squamous cell carcinoma by downregulating macrophage erythroblast attacher

Abstract: Aims: This study aimed to identify the correlation and molecular mechanism between TBC1 domain family member 14 (TBC1D14) and lymph node metastasis (LNM) in head and neck squamous cell carcinoma (HNSCC). Methods: Whole transcriptome sequencing of HNSCC tissues with or without LNM was performed. TBC1D14 expression was quantified in HNSCC tissues. The role of TBC1D14 in HNSCC migration, invasion, autophagy, and LNM was investigated by wound healing, Transwell, western blotting, immunofluorescence, and transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Specifically, the expression level of novel_circ_0010160 rapidly decreased from the PP to the EL and then slowly increased from EL to PL. Previous studies on TBC1D14 (parental gene of novel_circ_0010160) demonstrated its important role in cancer cell autophagy ( 43 , 44 ). This evidence suggests that novel_circ_0010160 may also function similarly in sheep MEC autophagy and would make a prime candidate for future research, especially in the non-lactation period.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the expression level of novel_circ_0010160 rapidly decreased from the PP to the EL and then slowly increased from EL to PL. Previous studies on TBC1D14 (parental gene of novel_circ_0010160) demonstrated its important role in cancer cell autophagy ( 43 , 44 ). This evidence suggests that novel_circ_0010160 may also function similarly in sheep MEC autophagy and would make a prime candidate for future research, especially in the non-lactation period.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results from the meta-analysis, INAFM1, HCFC1R1, and METTL26 were downregulated, and ATP6V0D2, TBC1D14, OXCT1, ALDH6A1, FAM160A1, and NCR3LG1 were upregulated in GMFB overexpressed Caki-2 cells ( Figures 5C, D ). The validated DEGs with GMFB co-expression may participate in multiple pathways in KIRC biology, including enhancing response in KIRC cell to NK cell (NCR3LG1) ( 46 ), negatively regulating autophagy (TBC1D14) ( 47 ), and being regulated by lactate (ATP6V0D2) ( 48 ) in TMEs.…”
Section: Discussionmentioning
confidence: 99%
“…In HNSCC, TBC1D14 inhibits autophagy by downregulating the expression of MAEA. Overexpression of TBC1D14 inhibits autophagy by reducing the level of Lc3-II protein, increasing the level of p62 protein, and inhibiting the formation of autolysosomes, thus playing a role in anti-HNSCC metastasis [ 97 99 ]. Circ-PKD2 can increase the sensitivity of oral squamous cell carcinoma to cisplatin by inhibiting miR-646.…”
Section: Mechanisms Of Cell Death In Hnsccmentioning
confidence: 99%